ETHICAL GUIDELINES FOR ADOPTION SOCIAL WORKERS IN SOUTH AFRICA: THE DELPHI PROCESS - Pieterse, Katinka; Malan, Hanelie (Social Work, 2023)
Adoption involves dealing with legal and ethical complexities, competing rights and addressing the long-term implications for those involved. The principle of the best interests of children and protecting their rights must guide the process. Currently, no ethical guidelines are in place to address South African adoption practices. This article focuses on the findings of a rapid review of relevant national and international ethics documents and adoption guidelines. The Delphi method was used to identify the challenges in adoption-related practices, as well as to develop and refine ethical guidelines for South African adoption social workers, to be included in the South African Council for Social Service Professions Policy Guidelines for Course of Conduct, Code of Ethics, and the Rules for Social Workers.